Active learning pedagogy for enriching economics students' higher order thinking skills - Sekwena, Gailele L. (Society for Research and Knowledge Management Ltd, 2023)
This paper advances active learning as a pedagogic praxis in Economics education to enrich students’ critical and higher order thinking skills (i.e., analysis, evaluation, and synthesis). The paper is grounded within Critical Theory (CT) as a theoretical lens, which gives this intellectual piece an impetus to propagate empowerment and transformation as guiding principles. The paper adopted Participatory Action Research (PAR) as a methodological approach to generating data. The two overarching research questions that developed the intellectual elements of this paper are: what are the challenges faced by Economics students in responding to higher order questions? How can active learning pedagogy be used to enrich Economics students’ critical and higher order thinking skills? A thematic analysis technique was used to analyse the discourses generated. Research shows that students find it challenging to respond to higher order questions and that Economics teaching is predominantly skewed towards the conventional lecture approach or the teacher-centred method, which often does not create opportunities for students to be actively engaged in the teaching and learning process, thus leaving them as passive recipients of knowledge. Based on the findings, this paper argues for active learning as a more unconventional pedagogy in Economics teaching to empower students to respond to higher order questions.
Keywords: Active learning; Economics education; Higher order thinking; Student engagement; Economics -- Study and teaching -- South Africa; Economics -- Study and teaching (Higher) -- South Africa